Significant effect of TiF3 on the performance of 2NaAlH4+Ca(BH4)2 hydrogen storage properties. (13th August 2019) - Mustafa, N.S.; Ismail, M.
Abstract: Titanium fluoride (TiF3 ) is doped into the reactive hydride composite of 2NaAlH4  + Ca(BH4 )2 by ball milling to enhance the hydrogen storage properties of the composite system. NaAlH4 and Ca(BH4 )2 phases were fully transformed to Ca(AlH4 )2 and NaBH4 phases after the ball-milling process (6 h). Four major stages were discovered in the undoped and TiF3 -doped system, which is corresponding to; (i) Ca(AlH4 )2, (ii) CaAlH5, (iii) CaH2 and (iv) NaBH4, respectively. The addition of TiF3 to the studied composite resulted in both reduced decomposition temperature and enhanced sorption kinetics compared with the undoped composite. The onset desorption temperature was reduced from 125 °C to 60 °C for the first stage in the TiF3 -doped composite, compared with the undoped composite. From differential scanning calorimetry analysis, the decomposition temperature for all stages has shifted to a lower temperature after doping with TiF3 . The activation energy has greatly reduced by 63.6 and 21.9 kJ/mol for CaAlH5 and NaBH4 stages, respectively, as compared with the undoped 2NaAlH4  + Ca(BH4 )2 composite. During the dehydrogenation process, the formation of new active species of Al3 Ti together with CaF2 played a vital role in accelerating the reactions in 5 wt% TiF3 doped to the studied composite system. Highlights: The addition of TiF3 reduces the onset decomposition temperature. The ab/desorption kinetic is also improved as compared to the undoped composite. The formation of new products, Al3 Ti and CaF2 play a synergetic catalytic role.